458 road safety policy initiative in Selangor: 30 kmh speed limit in school zones - K.C. Mani, Kulanthayan (BMJ Publishing Group, 2024)
Background The proposed 30 kmh speed limit in school zones is being outlined under the Global Plan Decade of Action for Road Safety 2021–2030 for the safety of pedestrians. This was echoed by Ministry of Transport Malaysia via the Malaysia Road Safety Plan 2022–2030 highlighting the importance of speed reduction. Objective The aim of the policy paper was to get the State Government of Selangor in Malaysia to explore and consider implementing the 30 kmh speed limit in school zones. Policy Analysis: The rationale behind this call was based on a human can absorb maximum up to 30 kmh transfer of speed energy during a road crash and anything above can lead to fatal crash. School zones are one of the main primary areas for pedestrian movements for children. Every child irrespective of their travel mode choice are pedestrians at the entry and exit of the school gate where their vehicles drop and pick them up. This is the most crucial zone as it involves the largest conflict points and interactions between human and vehicles in a concentrated zone. Policy Implications There are many schools in the state and thus all motorists will have an opportunity to drive slowly below 30 kmh in these zones. Once their vehicle speed reduces, it will take some time and distance for it to increase. Thus, during this entire slow speed period, not only the child pedestrians are safe, but also the motorist themselves and all other road users too. This policy implication will also now draw traffic enforcement agencies presence in school zones. This will indirectly increase traffic compliance and make these zones a safe place not only for road but also across other areas including crime prevention. Conclusions The National Road Safety Council of Selangor on 26th December 2023 agreed for this new 30 kmh Speed Limit in School Zones speed initiative to be introduced in Selangor in 2024 with an area marked ‘Begin 30 kmh’ and ‘End 30 kmh’ in selected schools in phase 1. This is a success story of an academic research initiative translating into stakeholders’ engagements and leading towards a policy change at state level.